Urea‐Mediated Monoliths Made of Nitrogen‐Enriched Mesoporous Carbon Nanosheets for High‐Performance Aqueous Zinc Ion Hybrid Capacitors. Issue 16 (13th March 2022) - Shang, Ping; Liu, Min; Mei, Yingying; Liu, Yuanhao; Wu, Lisha; Dong, Yanfeng; Zhao, Zongbin; Qiu, Jieshan
Abstract: Aqueous zinc ion hybrid capacitors (aZHCs) are of great potential for large‐scale energy storage and flexible wearable devices, of which the specific capacity and energy density need to be further enhanced for practical applications. Herein, a urea‐mediated foaming strategy is reported for the efficient synthesis of monoliths consisting of nitrogen‐enriched mesoporous carbon nanosheets (NPCNs) by prefoaming drying a solution made of polyvinylpyrrolidone, zinc nitrate, and urea at low temperatures, foaming and annealing at high temperatures, and subsequent acid etching. NPCNs have a large lateral size of ≈40 µm, thin thickness of ≈55 nm, abundant micropores and mesopores (≈3.8 nm), and a high N‐doping value of 9.7 at.%. The NPCNs as the cathode in aZHCs provide abundant zinc storage sites involving both physical and chemical adsorption/desorption of Zn 2+ ions, and deliver high specific capacities of 262 and 115 mAh g −1 at 0.2 and 10 A g −1, and a remarkable areal capacity of ≈0.5 mAh cm −2 with a mass loading of 5.3 mg cm −2, outperforming most carbon cathodes reported thus far. Moreover, safe and flexible NPCNs based quasi‐solid‐state devices are fabricated, which can withstand drilling and mechanical bending, suggesting their potential applications in wearable devices. Abstract : Urea‐mediated monoliths made of nitrogen‐enriched mesoporous carbon nanosheets (NPCNs) are fabricated for high‐capacity zinc ion hybrid capacitors. The NPCNs with large lateral sizes up to 40 µm, well‐developed micropores and mesopores (≈3.8 nm), a thin thickness of 55 nm, and a remarkable N‐doping value of 9.7 at.% show excellent zinc storage performance.